The principle of complimentarity through the Roma Satute: a critical analysis of its content, implementation and application. Case study of the DRC - Kahimba, Kambale Dérick (Department of Public Law, 2022)
The analysis of the principle of the complementarity formula set out in the Rome Statute is at the heart of this dissertation. The research aims to critically reflect on the complementarity regime under the Rome Statute in relation to international crimes committed in the DRC since the incorporation of the Rome Statute into the Congolese legal system. This research argues that the implementation of the principle of complementarity poses difficulties of application, implementation, and interpretation and thus remains a less effective means of putting an end to international crimes. The findings of this research indicate an urgent need for the principle of complementarity being rethought by clarifying its content and scope. Victims of international crimes cannot to date rely on its implementation to obtain justice. This research adopts an essentially conceptual approach; moreover, the methodological approach adopted is that of qualitative research. This research calls for the principle of complementarity being rethought by clarifying its content and scope.